2015
DOI: 10.21608/eajbsa.2015.12932
|View full text |Cite
|
Sign up to set email alerts
|

Annual Generations and Population Fluctuation of Tomato Leaf Miner Moth Tuta absoluta (Meyrick) (Lepidoptera :Gelechiidae) in El-Behera Governorate, Egypt.

Abstract: Egypt is considered one of the important tomato producers in the world that has appropriate climate for tomato along year in three different plantation seasons viz., winter, autumn and summer. Tomato infestation with tomato leaf miners (TLM) reached 70% in El-Behera governorate in 2011. So current study aimed throw some lights on population fluctuation of TLM males along two year (2013-2014) and different seasons by using pheromone traps, in addition studying the effect of climatic factors (Maximum, minimum, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
2
2
0
Order By: Relevance
“…With average temperatures ranging between 20 and 35 ᵒC in this season, a higher number of larvae hatch from eggs to progress to further development. These results are in agreement with those reported by Tabikha andHassan (2015) andEl Hajj et al (2017). Introduced species generally have fewer natural enemies compared with native species (Torchin and Mitchell, 2004), and recent cases of invasive pests indicate that local antagonists need time to adapt to the invader, which leads to loss of production during this period (Giorgini et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…With average temperatures ranging between 20 and 35 ᵒC in this season, a higher number of larvae hatch from eggs to progress to further development. These results are in agreement with those reported by Tabikha andHassan (2015) andEl Hajj et al (2017). Introduced species generally have fewer natural enemies compared with native species (Torchin and Mitchell, 2004), and recent cases of invasive pests indicate that local antagonists need time to adapt to the invader, which leads to loss of production during this period (Giorgini et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…As a result of rising temperatures, the insect progressed faster through its biological stages because of the accumulation of degree-day values. Similar results regarding the number of generations have been reported in Lebanon and Egypt by El Hajj et al (2017) and Tabikha and Hassan (2015), who recorded shorter average generation periods (31.5 and 28.5 days/generation, respectively). This difference is possibly attributed to the warmer climate of these countries, where this pest concludes its cycle in a shorter period.…”
Section: Discussionsupporting
confidence: 89%
“…In Egypt, the aforementioned method was used to determine the number of field generations of the pink mealybug of sugar cane, Saccharicoccus sacchari (Cockerell) (Hemiptera: Pseudococcidae) (Ebieda et al, 2020). Tabikha and Abdel-Nasser (2015) The 2 nd generation began from April, 19 to June, 7 and lasted 50 days. The 3 rd generation was observed in the field from June, 14 to July, 26 and lasted 43days.…”
Section: Number Of Field Generationsmentioning
confidence: 99%
“…Also, Polat et al (2016) declared that T. absoluta may accomplish 5 generations in Çanakkale province, Turkey, through summer-winter growing season. In addition, previous studies indicated that T. absulata has up to 11 generations per year with three generations during each growing season of spring, summer and autumn (Tabikha and Hassan, 2015). In another study carried out in openfield tomatoes in Assiut region (Upper Egypt), it was shown that T. absoluta can have 13 generations per year (Mohamed, 2011).…”
Section: Discussionmentioning
confidence: 97%